2019
DOI: 10.1016/j.eucr.2019.100894
|View full text |Cite
|
Sign up to set email alerts
|

Urethral self-inserted sewing needle in a 14-year-old boy for autoerotic stimulation

Abstract: Urethral foreign bodies are rare in daily practice, especially in adolescents with no evident history of mental illness. The presentation is usually delayed and a wide variety of objects may be implicated. Treatment by minimally invasive procedures (endoscopy), if possible, is preferred to minimize bladder and urethral injuries and psychiatric evaluation is mandatory to detect an underlying mental disorder. Despite the available literature on self-inserted urethral foreign bodies; the case we report here of ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“… 3 The self insertion of foreign bodies in the scrotum or in the lower urinary tract can have various causes, including psychological and psychiatric factors such as mental illness, borderline personality disorder, and drug abuse, traumatic causes, and migration from other organs. 4 In our case the patient was suffering from schizophrenia, and under the command of an imaginary person, he would put objects into his scrotum. A screw slipped, and he wasn't able to remove it.…”
Section: Discussionmentioning
confidence: 77%
“… 3 The self insertion of foreign bodies in the scrotum or in the lower urinary tract can have various causes, including psychological and psychiatric factors such as mental illness, borderline personality disorder, and drug abuse, traumatic causes, and migration from other organs. 4 In our case the patient was suffering from schizophrenia, and under the command of an imaginary person, he would put objects into his scrotum. A screw slipped, and he wasn't able to remove it.…”
Section: Discussionmentioning
confidence: 77%
“…Among pediatric cases, selfintroduction of FBs may indicate underlying psychiatric illnesses, accidental insertions, sexual stimulation, or mere curiosity. A wide variety of self-inserted FBs include needles, magnetic beads, metallic pins, hair clips, pencils, electric wire, and more (1)(2)(3)(4)(5)(6)(7)(8)(9)(10).…”
Section: Discussionmentioning
confidence: 99%
“…Urethral self-insertion of foreign bodies (FBs) in children are occasionally reported (1)(2)(3)(4)(5)(6). The goal of management is to remove FBs with minimal or no urethral morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Self-insertion of needles are rarely reported as they lead to sharp pain and blood urine rather sexual excitation. Zaghbib S et al 3 described a 14-year-old boy with urethral self-insertion of a sewing needle who complained of dysuria for 3 days. Park S et al 4 reported a boy with a urethral needle who had no remarkable symptoms.…”
Section: Discussionmentioning
confidence: 99%